The Effect of Gimkit Gamification on Students Mastery of Ether Nomenclature and Properties in Organic Chemistry - Andini Chairunisa; Catrin Wivia Irianah; Felizha Nazwa Zulkarnain Nazwa Zulkarnain; Nayla Putri Handayani; Rafa Sabirah (Edu Science Indonesia, 2024)
This study aims to analyze the effectiveness of gamification using the Gimkit platform in improving students’ understanding of ether concepts in Organic Chemistry. Ether material, including nomenclature, structure, physicochemical properties, and basic reactions, is often perceived as challenging due to its abstract nature and the need for strong conceptual understanding. Therefore, alternative learning approaches are required to enhance student engagement and learning motivation. A mixed-methods approach was employed involving 60 undergraduate pharmacy students. Participants completed two sequential learning evaluations: a conventional assessment using Google Forms and a gamified assessment conducted through Gimkit with equivalent content coverage. The results showed that students achieved higher average scores in the gamified assessment than in the conventional test. Students also reported increased motivation, active participation, and improved understanding of ether concepts. These findings indicate that Gimkit-based gamification positively affects both learning outcomes and students’ learning experiences and has strong potential as an effective instructional strategy in Organic Chemistry education, particularly for ether-related material in pharmacy programs.